Predictors of postinjury acute respiratory distress syndrome: Lung injury persists in the era of hemostatic resuscitation. Issue 2 (August 2019) - Kornblith, Lucy Z.; Robles, Anamaria J.; Conroy, Amanda S.; Redick, Brittney J.; Howard, Benjamin M.; Hendrickson, Carolyn M.; Moore, Sara; Nelson, Mary F.; Moazed, Farzad; Callcut, Rachael A.; Calfee, Carolyn S.; Cohen, Mitchell Jay
Abstract : BACKGROUND: Acute respiratory distress syndrome (ARDS) following trauma is historically associated with crystalloid and blood product exposure. Advances in resuscitation have occurred over the last decade, but their impact on ARDS is unknown. We sought to investigate predictors of postinjury ARDS in the era of hemostatic resuscitation. METHODS: Data were prospectively collected from arrival to 28 days for 914 highest-level trauma activations who required intubation and survived more than 6 hours from 2005 to 2016 at a Level I trauma center. Patients with ratio of partial pressure of oxygen to fraction of inspired oxygen of 300 mmHg or less during the first 8 days were identified. Two blinded expert clinicians adjudicated all chest radiographs for bilateral infiltrates in the first 8 days. Those with left-sided heart failure detected were excluded. Multivariate logistic regression was used to define predictors of ARDS. RESULTS: Of the 914 intubated patients, 63% had a ratio of partial pressure of oxygen to fraction of inspired oxygen of 300 or less, and 22% developed ARDS; among the ARDS cases, 57% were diagnosed early ( in the first 24 hours), and 43% later. Patients with ARDS diagnosed later were more severely injured (ISS 32 vs. 20, p = 0.001), with higher rates of blunt injury (84% vs. 72%, p = 0.008), chest injury (58% vs. 36%, p < 0.001), and traumatic brain injury (72% vs. 48%, p < 0.001) compared with the no ARDS group. In multivariate analysis, head/chest Abbreviated Injury Score scores, crystalloid from 0 to 6 hours, and platelet transfusion from 0 to 6 hours and 7 to 24 hours were independent predictors of ARDS developing after 24 hours. CONCLUSIONS: Blood and plasma transfusion were not independently associated with ARDS. However, platelet transfusion was a significant independent risk factor. The role of platelets warrants further investigation but may be mechanistically explained by lung injury models of pulmonary platelet sequestration with peripheral thrombocytopenia. LEVEL OF EVIDENCE: Prognostic study, level IV. Abstract : Supplemental digital content is available in the text.